A Shareholder Activity: Types of Control, Gaining and Using it - Makharoblisvili, Giorgi (Journal of Law, 2023)
The article analyzes control as a methodical mean of practical implementation of shareholder activism, the ways of obtaining it and forms of use in the corporate-legal dimension. In corporate law, control is understood in several directions. Its corporate sense leads to the mutual separation of ownership and control, management and holding a controlling stake by a shareholder under the authority of the JSC. The three-level classification of control is based on positive corporate law, which is developed by the best international practices of corporate management and the requirements of capital market law. The research thesis is centered on the legal, and in certain cases, economic categories of a shareholder controlling stake. In the article, the term "control" is analyzed with regard to its accession and use by a person (a shareholder) inclined to take control over the main material and procedural transactions and the control premium. The method of comparative legal research, systematic and teleological definition of the norm makes it possible to cover the basic scientific range of control in the JSC.